Residence Time and Transformation of Warm Circumpolar Deep Water on the Antarctic Continental Shelf. Issue 20 (19th October 2021) - Tamsitt, V.; England, M. H.; Rintoul, S. R.; Morrison, A. K.
Abstract: Inflow of warm modified Circumpolar Deep Water (CDW) onto the Antarctic continental shelf and into ice shelf cavities is a key driver of Antarctic ice shelf mass loss. While recent research has advanced understanding of CDW heat transport onto the continental shelf, the fate of CDW on the shelf is less understood. Here, we use Lagrangian particle tracking in an ocean‐sea ice model without ice shelf cavities to map the residence time of CDW on the Antarctic continental shelf. Mean residence times vary from < 1 month in the East Antarctic to > 1 year in the West Antarctic. In regions of dense water formation, transformation of CDW on the shelf limits access of CDW to ice shelves, despite strong onshore CDW heat transport. Elsewhere transformation of CDW on the shelf is weak, implying that temperature on the shelf is limited by heat transport onto the shelf or the offshore heat reservoir. Plain Language Summary: Antarctic ice shelf melt is accelerating and is linked to the inflow of warm ocean waters that melt ice shelves from below. Multiple processes regulate the amount of warm water that reaches the Antarctic ice shelves, and the relative importance of these processes in different regions is not well known. Here, we conduct a virtual particle tracking experiment in a state‐of‐the‐art ocean model to trace the pathways and timescales of warm water on the Antarctic continental shelf. We find that there is a large regional variation in how long warm waters spend on the continental shelf from less than a month to well over a year. In the regions along the continental slope where very dense water formed near the coast flows off the shelf to the abyssal ocean, this is balanced by a strong inflow of warm water onto the continental shelf, which is rapidly converted to denser water, limiting the heat from reaching the ice shelves. Elsewhere warm water can remain on the continental shelf unmodified for a long time, so the heat available for ice shelf melt is instead limited by the strength of the flow of warm water onto the continental shelf. Key Points: Particle tracking in an ocean model shows Circumpolar Deep Water (CDW) residence times on the Antarctic shelf range from a month to several years Water mass transformation limits CDW access to ice shelves in Dense Shelf Water formation regions, despite strong onshore CDW transport In warm shelf regions, long residence times of CDW are associated with weak water mass transformation